Diosdado Magno Lorenzo art rebel to legend (Makati City Philippine Italian Association, 2009)
This 24 minute documentary traces the life of Diosdado Magno Lorenzo, Leading pioneer of modernist art in the Philippines and one of the greatest painters in the country has ever produced--container.
DVD.